The Waste Management of Non-Organic Waste by Residents of Laut Dendang Region - Nur Hakiki (International Journal of Educational Practice and Policy, 2023)
This study is aiming to observe the condition and utilization of non-organic waste by the residents of Laut Dendang Region. This study is implementing qualitative method. The data collection techniques used observation and interviews technique. The environment is very closely related to humans. Non-organic waste is typical waste that cannot be decomposed by bacteria and takes a very long time to decompose. The increasing volume of waste requires prospered handle in which management of Non-organic waste that does not use the method will have a very dangerous impact to the environment and human health. The most dangerous waste is Non-organic waste which produced by households and industry. The use of Non-organic waste requires ways that must be carried out by the residents of Laut Dendang Region to maintain the environment and public health.